Special edition using TCP/IP (Que, 2002)
Special Edition Using TCP/IP, 2E is the practical guide to applications of TCP/IP, including utilities for operation, troubleshooting, and management, with insight into future applications such as Voice over IP and VPNs. It includes current TCP/IP draft standards and future work planned. Clear illustrations of practical utilities enable the reader to understand both the technology and applications together from a single source. It includes current scaling problems in the Internet like addressing and routing. Both short-term solutions and long-term solutions for these problems are discussed.